Reduction in the potential distribution of bee species in low latitudes under different climate change scenarios: conservation implications - Tang, Xinggang; He, Zheng; Deng, Yue; Yuan, Yingdan; Zeng, Kaiming (Frontiers in Ecology and Evolution, 2025)
To quantify the climate-change impact on bees and guide conservation planning, we employed ecological niche modeling (ENM) driven by three representative concentration pathways (RCP 4.5, 6.0 and 8.5) and three general circulation models (CCSM4, HadGEM2-AO and MIROC-ESM-CHEM). Across all scenarios and GCMs, suitable climatic space for every bee species is projected to contract, with the steepest declines in low-latitude regions. Range contractions vary from 8% to 87%, with wide-ranging species exhibiting greater resilience. Furthermore, Mean annual temperature (Bio1), annual precipitation (Bio12) and elevation collectively explain the largest share of interspecific distributional dynamics for each bee species. The median elevation of suitable pollinator habitat is projected to rise by 35 to 450m. The suitable centroids of bee species are expected to migrate 65 to 137 km south-eastwards, except for A. florea. Model projections indicate a widespread decline in environmental suitability for pollinators. Alarmingly, projected suitable occupied by habitat protected areas is relatively low, implying limited conservation efficacy under future climates. Accordingly, our findings provide a quantitative foundation for stakeholders to maximize the ecological and economic value of pollinators and develop smarter plant protection strategies in a warming world.